Management of a 5-Year-Old Patient with Pancreatic Serous Cystadenoma: A Rare Case Report - Dedi Rahmad Harahap; Ismar Ismar; Tubagus Odih Rhomdani Wahid; Dedy Satria; Arnadi Arnadi; Welly Zulfikar; Eddy Ahmad Syahputra; Andrea Valentino; Sinta Chaira Maulanisa (Jurnal Ners, 2026)
Introduction: Pancreatic serous cystadenoma is a benign primary pancreatic cystic neoplasm that typically presents asymptomatically. It is rare in the pediatric population and often poses diagnostic challenges. Case Report: A 5-year-old girl presented to the emergency department at Arifin Achmad Hospital with severe pain in the left upper quadrant of the abdomen, which had persisted for 5 days. Clinical examination revealed swelling and erythema in the epigastric region. Imaging studies identified cystic lesions in the pancreas. The patient underwent a pancreatectomy, and the pathological examination confirmed the diagnosis of pancreatic serous cystadenoma. Conclusion: Diagnosing pancreatic masses requires a comprehensive evaluation, with radiological imaging being crucial for accurate diagnosis and treatment planning. For lesions located in the caudal region of the pancreas, distal pancreatectomy is the recommended surgical approach.